Plasma calcitonin gene-related peptide and nitric oxide predict therapeutic response to amlodipine in pediatric primary hypertension - Wang, Hui; Lin, Yao; Wang, Yuting; Shen, Chen; Li, Yaqi; Liu, Yang; Shi, Lin (Frontiers in Pharmacology, 2024)
BackgroundThere is a lack of suitable predictive markers for assessing the efficacy of amlodipine in treating children with primary hypertension. This study aimed to explore whether plasma calcitonin gene-related peptide (CGRP) and nitric oxide (NO) could predict the effectiveness of amlodipine in pediatric primary hypertension.MethodsThis study enrolled 74 children and adolescents with primary hypertension who were prescribed amlodipine monotherapy, and after 4 weeks of treatment, they were divided into responders and non-responders according to blood pressure. Baseline data differences between the two groups were analyzed, followed by binary logistic regression to assess the correlation between significant variables and therapeutic efficacy. The receiver operating characteristic curve was used to evaluate the predictive efficacy, and the nomogram model was established to predict therapeutic response to amlodipine.ResultsThe responders exhibited lower body mass index, C-peptide and plasma CGRP levels, and higher NO levels compared to the non-responders (p < 0.05). Multivariable logistic analysis revealed that plasma CGRP and NO were independently associated with the therapeutic response to amlodipine, showing a higher predictive performance when used in combination (AUC: 0.814, 95% CI 0.714–0.914) with a predictive sensitivity of 86.5% and specificity of 70.1%. The nomogram model displayed good calibration, and the decision curve analysis indicated this model led to net benefits in a wide range of threshold probability.ConclusionCGRP and NO may be valuable biomarkers for predicting amlodipine effectiveness in the treatment of pediatric primary hypertension, while the nomogram model indicates excellent predictive value.